Assessing shelf aggregate environmental compatibility and suitability for beach nourishment: A case study for Tuscany (Italy). Issue 1 (15th April 2015) - Bigongiari, Nicola; Cipriani, Luigi E.; Pranzini, Enzo; Renzi, Monia; Vitale, Giovanni
Highlights: Beach nourishment practices are a key aspect in coastal management plans. Current laws and technical guidelines on this matter evidence some gaps. Integrated approach evidences advantages to the decision-making process. Only dredging intended to manage >1, 000, 000 m 3 of aggregates are sustainable. Abstract: Beach nourishment practices are a key aspect in coastal management plans for stakeholders and communities. Stemming from a concrete case-study (Tuscany), this research analyzes: (i) principal problems of current law regulating dredging, (ii) gaps in technical guidelines, (iii) advantages of integrated approaches to the decision-making process, (iv) possible applicable nourishment options and their costs and benefits. Our results show that sand compatibility is driven mainly by grain-size stability due to the occurrence of lower pollution levels in off-shore deposits than in threatened beaches, thus current laws and guidelines should be improved to fill the evident gap in the evaluation process and to include a more complete approach to data evaluation and an integrated approach to ecotoxicity evaluation, which is relevant in cases of geochemical anomalies. The cost-benefit analysis performed indicates that only dredging intended to manage more than 1 million m 3 of aggregates would represent a real advantage for local communities.